2019
DOI: 10.3390/cancers11121995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PMEPA1 Isoforms (a and b) as Selective Inhibitors of Androgen and TGF-β Signaling Reveals Distinct Biological and Prognostic Features in Prostate Cancer

Abstract: Dysfunctions of androgen/TGF-β signaling play important roles in prostate tumorigenesis. Prostate Transmembrane Protein Androgen Induced 1 (PMEPA1) inhibits androgen and TGF-β signaling via a negative feedback loop. The loss of PMEPA1 confers resistance to androgen signaling inhibitors and promotes bone metastasis. Conflicting reports on the expression and biological functions of PMEPA1 in prostate and other cancers propelled us to investigate isoform specific functions in prostate cancer (PCa). One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…The analysis of predicted structural features of PMEPA1 protein contains the following three domains: (i) Luminal (N-terminal domain), (ii) Membrane spanning (Transmembrane domain), and (iii) Cytoplasmic. N-terminal domain shows length polymorphisms among the isoforms [ 11 ]. The transmembrane and cytoplasmic domains show highly conservative amino acid sequences.…”
Section: Structure and Biochemical Features Of Pmepa1 mentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis of predicted structural features of PMEPA1 protein contains the following three domains: (i) Luminal (N-terminal domain), (ii) Membrane spanning (Transmembrane domain), and (iii) Cytoplasmic. N-terminal domain shows length polymorphisms among the isoforms [ 11 ]. The transmembrane and cytoplasmic domains show highly conservative amino acid sequences.…”
Section: Structure and Biochemical Features Of Pmepa1 mentioning
confidence: 99%
“…Assessments of relative expression of each isoform indicated that PMEPA1-a was most abundant followed by PMEPA1-b and PMEPA1-c in prostate cancer cell lines and human prostate tumor tissues which are defined as major isoforms [ 1 , 11 ]. PMEPA1-d and PMEPA1-e isoforms are marked as minor isoforms with lower transcript levels detected [ 1 ].…”
Section: Expression Of Pmepa1 Isoformsmentioning
confidence: 99%
See 3 more Smart Citations